Examining the Use of Verbal Teacher Feedback in Physical Education Lessons - Rachel Mackinney (Education Sciences)
This study analysed the frequency and nature of verbal feedback given by physical education (PE) teachers in a secondary school, focusing on the influence of teacher gender, experience, and student learning stage. Eight PE teachers (four male, four female) were observed across 24 lessons, with each teacher observed three times. Feedback was systematically coded using a structured framework for evaluating coaching practises. The results revealed variations in feedback patterns based on teacher experience, gender, and student age. Female teachers provided more specific positive feedback (28%) compared to male teachers (23%). Younger, less experienced students received more corrective feedback (years 7 and 8: 18.7%; years 9 and 10: 12.7%), highlighting the importance of targeted instruction in early learning stages. Additionally, less experienced teachers used less corrective feedback (15%) than their more experienced counterparts (25.6%), suggesting a need for professional development in feedback strategies. These findings emphasise the role of tailored feedback in PE to optimise student learning and engagement.